Upaya Meningkatkan Partisipasi Pemilih Pemula Pemilu 2024 Melalui Sosialisasi Surat Suara di SMA PGRI 2 Denpasar - Davi, Nadine Kalina; Wibawa Putra, Komang Satria; Ariwangsa, I Gusti Ngurah Oka; Gama, Adie Wahyudi Oktavia; Permana, Gusi Putu Lestara (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
The 2024 elections to elect the President and Vice President, Members of the DPR RI, Members of the DPD RI, Members of the Provincial DPRD, and Members of the Regency/City DPRD will be held simultaneously throughout Indonesia on February 14th, 2024. According to data from the General Election Commission (KPU), the Millennial and Z generations dominate the vote in this election with 114 million voters or approximately with a total of 56% of all voters, so it can be ensured that for the success of the election, the participation of these two generations is very important. The service method was carried out by providing election outreach to 100 students at SMA PGRI 2 Denpasar on Tuesday, January 30 2024 at 10.30 - 11.00 WITA with the stages of providing material and a question and answer session. The results obtained were that many students already knew that the 2024 elections would take place and the location of each voting place. However, most students do not know details such as the types of ballot papers and the administrative procedures for transferring votes. After the socialization activities were completed, the students understood the message that their voting rights were important and that they should not abstain.